Peningkatan Kemampuan Motorik Halus melalui Permainan Melipat Pada Kelompok B TK Negeri Pembina I Mojosari - Faridha Shafira; Sri Setyowati (Journal on Education, 2023)
This study aims to improve fine motor skills through folding games in group B1 at TK Negeri Pembina I Mojosari. This research is a classroom action research using the Kemmis and Mc Taggart methods, which include planning, action, observation and reflection stages. The research subjects were 20 children consisting of 12 boys and 8 girls. Methods of data collection using observation. The data collection instrument is an observation sheet. The success criterion in this study was 80%. The data analysis technique uses quantitative and qualitative data analysis. The results showed that children's fine motor skills could be improved through folding activities. This can be seen from the fine motor skills of the children who reached BSH (Developing According to Expectations) experienced an increase from 3 children (17%) in Cycle I to 5 children (27.8%) in Cycle II, meaning an increase of 13.8 %. In addition, the fine motor skills of children who reached BSB (Very Well Developed) experienced an increase from 5 children (28%) who achieved BSB in Cycle I, to 11 children (61.1%) in Cycle II, meaning an increase of 33 .1 %.